2010
DOI: 10.1177/2150135110361361
|View full text |Cite
|
Sign up to set email alerts
|

Neoaortic Valve Function 10 to 18 Years After Arterial Switch Operation

Abstract: Anatomical correction is a procedure of choice for transposition of the great arteries (TGA) in neonates. During surgery, the aorta and pulmonary artery are switched-the native pulmonary valve becomes the neoaortic valve. The fate of this valve remains uncertain. Many reports suggest that its ability to function worsens with time after surgery. Of 519 patients with TGA operated on between 1991 and 2008, 161 met inclusion criteria for this retrospective study and were followed 10 years or more to assess neoaort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Our initial search yielded 344 unique citations ( Supplemental Table 1 ); among these, 30 fulfilled our eligibility criteria ( Figure 1 ). 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Characteristics of each study and their participants are shown in Table 1 . The 30 included studies comprised a total of 6,169 patients and were conducted in 13 different countries across 3 continents.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial search yielded 344 unique citations ( Supplemental Table 1 ); among these, 30 fulfilled our eligibility criteria ( Figure 1 ). 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Characteristics of each study and their participants are shown in Table 1 . The 30 included studies comprised a total of 6,169 patients and were conducted in 13 different countries across 3 continents.…”
Section: Resultsmentioning
confidence: 99%
“…Hypotheses have been made about histomorphological differences between the great vessels in TGA, the position of the pulmonary valve in the systemic circulation, surgical injury to the vasa vasorum and ischemic lesions to the arterial wall and geometrical factors of arterial root anastomosis and leaflet coaptation, as well as primary root dilatation followed by somatic growth. [6][7][8][9][10][11] In our experience in the mid-and long-term follow-up, a common finding in patients who developed moderate to important neoaortic root dilatation and neoaortic valve regurgitation was the presence of APM observed during ASO, especially in patients with complex variants of TGA. We believe that APM plays an important role in the mechanism of neoaortic root dilatation and valve regurgitation by altering the geometry of the great vessel root and affecting fluid dynamics in this structure, leading to changes in the wall shear stress, promoting vascular remodeling and susceptibility to dilatation.…”
mentioning
confidence: 76%
“…Nevertheless pathophysiological mechanisms for neoaortic root dilatation and development of moderate‐to‐severe neoaortic valve regurgitation are probably multifactorial and not completely elucidated. Hypotheses have been made about histomorphological differences between the great vessels in TGA, the position of the pulmonary valve in the systemic circulation, surgical injury to the vasa vasorum and ischemic lesions to the arterial wall and geometrical factors of arterial root anastomosis and leaflet coaptation, as well as primary root dilatation followed by somatic growth 6–11 …”
mentioning
confidence: 99%
“…Michalak, et al followed 519 for 10 years and observed that the frequency of significant regurgitation increased from 9% 1 year after the operation to 47% at the most recent follow-up [23]. No severe regurgitation necessitating reoperation was observed.…”
Section: Risk Factors Of Armentioning
confidence: 99%